An Integrative Model of Curriculum Development Based on Industrial Structure Analysis and External Competitiveness: A Systematic Review of the Literature - Yulya Astuthi; Erny Roesminingsih; Nuphanudin Nuphanudin (Journal of Vocational, Informatics and Computer Education, 2026)
This study aims to develop an integrative perspective on curriculum development by incorporating external environment analysis and industry structure to enhance the relevance and competitiveness of education systems. The research is motivated by the growing mismatch between educational outcomes and labor market demands, as well as the increasing influence of technological transformation and global competition on curriculum design. To address this gap, this study employs a Systematic Literature Review (SLR) approach guided by the PRISMA framework, analyzing approximately 30 peer-reviewed journal articles. The findings reveal three dominant clusters: curriculum and education, industry and competitiveness, and digital transformation. The results indicate that curriculum functions as a central node connecting industry needs, technological advancements, and competency development. The study confirms that aligning curriculum design with industry structure and external environmental factors significantly improves graduate employability and educational quality. However, the findings also highlight limitations related to reliance on secondary data and the absence of empirical model testing, which may affect generalizability. This research contributes originality by integrating educational theory with strategic management frameworks, particularly industry analysis and competitive forces, into curriculum development discourse. The proposed integrative model offers practical implications for policymakers and educational institutions in designing adaptive, industry-responsive curricula. Future research is recommended to empirically validate the model and expand its application across different educational contexts and sectors.